LEGAL PROTECTION FOR CHILDREN ADDICTED TO ONLINE GAMES IN THE DIGITAL AGE OF GENERATION ALPHA: IMPACTS AND PREVENTIVE SOLUTIONS - Muhammad Yusril Irza; Ikama Dewi Setia Triana; Aniek Periani (Universitas Wijayakusuma Purwokerto, 2026)
The development of digital technology in the era of globalization has brought significant changes to the lives of children, especially Generation Alpha, who have grown up with internet access and digital devices from an early age. One increasingly worrying impact is the increasing excessive use of online games, leading to addiction. Online game addiction not only impacts academic achievement but also affects children's mental health, social behavior, and emotional development. In fact, the World Health Organization has classified game addiction as a gaming disorder, an addictive behavioral disorder that requires serious attention. This community service activity aims to analyze the dangers of online games for Generation Alpha in the digital era and examine the role of parents and educators in preventing online game addiction. The method used is an educational approach through counseling and digital literacy education regarding the wise use of technology for students at the Pattanakansuksa Foundation School in Satun, Thailand. The results of the activity show that providing education about the negative impacts of online games can increase students' awareness of the risks of addiction and the importance of balancing digital activities with learning and social activities. Thus, synergy between parents, educators, and the school environment is the main key to protecting Generation Alpha from the negative impacts of online games and realizing healthy, responsible technology use that is oriented towards children's character development.